A bioinspired, photostable UV-filter that protects mammalian cells against UV-induced cellular damage. Issue 80 (18th September 2019) - Martin, Camille A.; Rezaeeyazdi, Mahboobeh; Colombani, Thibault; Dinneen, Sean R.; Kumar, Amrita; Bencherif, Sidi A.; Deravi, Leila F.
Abstract : We demonstrate the application of xanthommatin (Xa), a biochrome present in arthropods and cephalopods, as an alternative chemical UV-filter that is cytocompatible while maintaining photostability and photoprotective properties. Abstract : While commercially available suncare products are effective at absorbing ultraviolet (UV)-light, recent studies indicate systemic toxicities associated with many traditional chemical and physical UV-filters. We demonstrate the application of xanthommatin, a biochrome present in arthropods and cephalopods, as an alternative chemical UV-filter that is cytocompatible while maintaining its photostability and photoprotective properties.